Interactive Teaching Methods as a Means of Effective Formation of Schoolchildren's Literary Skills (Journal of Pedagogical Inventions and Practices, 2023)
Interactive teaching methods have been proven to be effective in developing schoolchildren's literary skills. These methods involve students actively participating in the learning process, which encourages critical thinking, creativity, and communication. This article explores different interactive teaching methods, such as reading aloud, role-playing, writing workshops, and technology, that can be used to develop literary skills in schoolchildren. By using these methods, teachers can create a positive and engaging learning environment that fosters the development of important skills needed for success in life.